Digital strategy and adaptive leadership: optimizing talent management in human capital in local government survey LAN 2025 - Harmen, Hilma; Ampun, Grace Analita Febrina Anak; Situmorang, Listem Wisiska; Zahra, Saffanah Alya; Atikah, Dhiya; AlFarisi, Mhd Rasyid; Azalia, Siti Salwa (EDUCTUM: Journal Research, 2026)
This study aims to analyze digital strategies and adaptive leadership in optimizing talent management as part of strengthening human capital in local governments. The background of this study is based on the results of the LAN 2025 Survey, which showed that the implementation of talent management in most local governments is still slow due to the lack of integration between policy, technology, and leadership. The research method used is descriptive qualitative with a literature study approach and content analysis of various secondary sources such as news, survey results, and previous research. The results show that strengthening talent management requires synergy between the implementation of the Digital Talent Management System (DTMS), adaptive leadership, open internal communication, and a culture of continuous learning. This strategy can create a transparent, innovative, and competency-based HR management ecosystem. Thus, the integration of digital strategies and adaptive leadership can strengthen the effectiveness of talent management in improving the performance of state civil servants and creating a resilient bureaucracy in the era of digital transformation.